Ethnic-cultural lexical and semantic field of «LIQUID» which is presented in Ukrainian (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
A field method research linguistic unit on the ethnoculchure background, to permit investigate linguistic system in her intergrity and establishment contact between vocabulary, what her to form. Article to scrutinize lexuco-sementic  field «Liquid» with position ethnoculchure Ukrainian people.
Keywords: lexuco-sementic field; micro field; conception zone; kernel near outlying area; zemote outlying area